Courting Controversy: The Problems Caused by Extrajudicial Speech and Writing - Moran, Jasmin (Victoria University of Wellington Law Review, 2015)
This article explores the problems for judicial impartiality that a judge's extrajudicial speaking or writing on legal matters may create. Examples from New Zealand and abroad demonstrate such extrajudicial commentary may lead to a finding of apparent bias or require that a judge recuse him or herself from hearing a case. The current regulation of extrajudicial speech, as ascertained from judicial conduct codes and case law, provides that judges can speak and write extrajudicially but must exercise caution in the tone and language they use. The article concludes that this is an appropriate approach and that the alternative of judicial silence is undesirable.